Effects of Environmental Factors on Carbon Stocks of Dry Evergreen Afromontane Forests of the Choke Mountain Ecosystem, Northwestern Ethiopia - Fikirte Asrat; Teshome Soromessa; Tesefaye Bekele; Rama Mohan Kurakalva; Sravya Sai Guddeti; David Russel Smart; Kristine Steger (International Journal of Forestry Research)
The purpose of this research was to quantify and compare carbon stocks in two selected dry evergreen montane forests of the Choke Mountain ecosystem that are under different management regimes. The study also attempted to assess the carbon stock along environmental gradients. The average carbon stock throughout the whole plots investigated in Anshirava forest (protected) was 180.18 t·ha−1 (53%) in AGB, 111.43 t·ha−1 (33%) in soil, 36.43 t·ha−1 (11%) in BGB, 6.09 t·ha−1 (2%) in USB, 2.69 t·ha−1 (1%) in litter, and 1.36 t·ha−1 (less than 1%) in DW. In Ziba forest (high human intervention), the average carbon stock was 106.71 t·ha−1 (44%) in AGB, 100.07 t·ha−1 (42%) in soil, 21.34 t·ha−1 (9%) in BGB, 5.41 t·ha−1 (2%) in USB, 4.82 t·ha−1 (2%) in litter, and 2.00 t·ha−1 (1%) in DW. The AGB had the greatest carbon share in both forests, followed by soil. In Anshirava and Ziba forests, the mean total carbon stocks (TCS) were 338.18 t·ha−1 and 240.36 t·ha−1, with CO2 equivalents of 1241.14 t·ha−1 and 882.12 t·ha−1, respectively. The study indicated a significant variation between the two forests. Anshirava forest has larger total carbon stocks than Ziba forest. For lower, medium, and higher altitudes, the total carbon stock variation along an altitudinal gradient was 289.67 t·ha−1, 347.93 t·ha−1, and 414.89 t·ha−1 in Anshirava forest and 270.99 t·ha−1, 204.24 t·ha−1, and 224.82 t·ha−1 in Ziba forest, respectively. As a result, a greater amount of carbon was stored at higher altitudes in Anshirava and at lower altitudes in Ziba, with no significant difference in both forests. The total carbon stock variation along slope gradient was 392.60 t·ha−1, 344.59 t·ha−1, and 295.49 t·ha−1 in Anshirava forest and 258.74 t·ha−1, 222.46 t·ha−1, and 171.46 t·ha−1 in Ziba forest for flat, intermediate, and steep slopes, respectively. This resulted in higher carbon being stored in flat slopes in both forests. Also, only at the Ziba site, a significant difference was found along the slope gradient. In each forest, eight distinct aspect facings were observed, with the western (W) aspect containing the highest value of total carbon stock in both forests. Lower values, on the other hand, were recorded in the south (S) and flat (F) aspects of Anshirava and Ziba forests, respectively. The slope aspects of both forests varied significantly. As a result, the research reveals that environmental factors have a significant impact on carbon stock value of Choke Mountain forest ecosystem, but the impact is not consistent among carbon pools.